Photovoltaic untuk Mesin Pengasap Ikan Berbasis Kearifan Pakan Lokal dalam Pencegahan Stunting di Desa Karangrejo Bonang Demak - Ismail, Munaf; Utom, Sukarno Budi; Rosyidah, Hanifatur (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
Posyandu Klitih Karangrejo Bonang Demak is a partner in community partnership empowerment that has health problems, namely stunted children in Karangrejo village, so that the health conditions of mothers and children need special attention. Maternal and child health that needs attention from many parties, especially in Karangrejo village because there are still children with stunting conditions. Bonang District has potential for marine products, because its area has sea and is a producer of tuna fish in Demak district. The purpose of this program is to improve maternal and child health by training the community in the skills of making smoked fish based on solar power or photovoltaic and the community's ability in marketing by optimizing internet marketing. Increasing community business opportunities, increasing community skills and abilities to start smoked fish production, besides that of course the expected results together are increased public health and no new stunting rates.